Determination of scattered radiation on general x-ray tabletop using dose mapping technique - Shahrul Nizam, Siti Nur Irdina Amalin; Abdul Majid, Zafri Azran; Sapuan, Abdul Halim; Jamaludin, Iqbal; Shah, Sayed Inayatullah; Che Azimin, Zulfaezal (Faculty of Medicine, 2026)
Scatter radiation is an essential parameter to be measured in diagnostic imaging, as it can degrade image quality and increase radiation exposure to both patients and healthcare personnel. Due to the invisible nature of X-rays, scatter radiation cannot be directly visualized and must be quantified using indirect measurement techniques such as dosimetry during patient exposure. This study investigates the distribution of scatter radiation on a general X-ray tabletop using a dose mapping technique, with a specific focus on the examination couch area where the patient is positioned during the imaging procedure.